Design of English Mobile Learning Platform Based on GSM-R Wireless Network Communication System - Xiaowei Liu; Hongjin Liu (International Journal of Antennas and Propagation)
Because the traditional English mobile learning platform has low student satisfaction and a long learning time, an English mobile learning platform based on the GSM-R wireless network communication system is designed. A GSM-R wireless network communication system is built through existing facilities, new facilities, and business-side facilities. Platform function modules are designed based on the communication system, including course resource management module, online examination management module, online Q&A management module, platform management module, and user login. Based on this module, the platform software is designed according to the three steps of database design, platform encryption technology, and learning recommendation algorithm to create the English mobile learning platform. The simulation experiment results show that the application of the designed platform can improve student satisfaction and improve student learning efficiency.